2011
DOI: 10.4028/www.scientific.net/amr.264-265.1050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PVD-Inserts Performance and Surface Integrity when Turning Ti-6Al-4V ELI under Dry Machining

Abstract: The great advancement in the development of carbide cutting tool with super-hard coating layers taken place in recent few decades, can improve the performance of cutting tool and machinability of titanium alloy. The turning parameters evaluated are cutting speed (55, 75, 95 m/min), feed rate (0.15, 0.25, 0.35 mm/rev), depth of cut (0.10, 0.15, 0.20 mm) and tool grade of PVD carbide tool. The results that tool life shows patterns of rapidly increase at the initial stage and gradually increased at the second sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It is reported the reducing trend in surface roughness with leading speed. 14–16 In another work, Ibrahim et al 17 stated that the higher speed machining exhibited a high temperature and it was responsible for microstructure and surface alteration of the machined workpiece. Karkalos et al 18 concluded that the low feed machining of Ti-alloys exhibited the lower magnitudes of roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported the reducing trend in surface roughness with leading speed. 14–16 In another work, Ibrahim et al 17 stated that the higher speed machining exhibited a high temperature and it was responsible for microstructure and surface alteration of the machined workpiece. Karkalos et al 18 concluded that the low feed machining of Ti-alloys exhibited the lower magnitudes of roughness.…”
Section: Introductionmentioning
confidence: 99%
“…but it has limitations like poor thermal conductivity and highly reactive at elevated temperature, etc., which makes it difficult to machine. 1,2,8,9,14,18 To overcome the above difficulties, the application of inexpensive multi-layer coated carbide cutting tool in machining Ti-6Al-4V ELI alloy is proposed in this paper because of superior properties of lubricating, thermal barrier and wear-resistant thus can protect the cutting tool wear and may enhance tool life. Very limited work has been noticed for machining investigation of Ti-6Al-4V ELI alloy till date.…”
Section: Introductionmentioning
confidence: 99%
“…Surface quality easily affected by the input parameters when machining on titanium alloy specially feed rate is the predominant factor for surface roughness. Due to the high hardness of Ti-6Al-4V ELI alloy and low thermal conductivity, a high amount of heat generated at the upper surface of the workpiece causes increased in the tool wear which damage the microstructure and surface integrity [5][6][7][8][9][10][11][12]. Karkaols et al [5] predicted the surface roughness of Ti-6Al-4V ELI alloy in a milling operation.…”
Section: Analysis Of Surface Roughnessmentioning
confidence: 99%
“…RSM method used to optimizes the input and output response and then compared the RSM and ANN models for more accurate prediction. Ibrahim et al [6][7][8][9] investigated the microstructure alterations and surface integrity during turning of Ti-6Al-4V ELI alloy in a dry cooling environment with coated carbide cutting insert. Found that when the temperature increases at cutting region it's damaged the upper machined workpiece surface and affected the surface microstructure.…”
Section: Analysis Of Surface Roughnessmentioning
confidence: 99%
“…Machined surface acceptable and free from physical damage viz; cracks and tears. Ibrahim et al (2011) explored that machining of titanium alloy at the high feed rate produced the high and uneven surface roughness but when the cutting speed increases surface roughness decreases. Ramesh et al (2008) explored that surface roughness increases due to high feed, but the increased cutting speed decreases the surface roughness.…”
Section: Introductionmentioning
confidence: 99%